Lower-intensity chemo-immunotherapy with cladribine, low-dose cytarabine, venetoclax and blinatumomab produces high response rates in patients with BCR::ABL1-negative B-cell / myeloid mixed phenotype acute leukemia - Roberta S. Azevedo; Wei-Ying Jen; Danielle Hammond; Fadi G. Haddad; Alexis Geppner; Ghayas C. Issa; Koji Sasaki; Jayastu Senapati; Elias Jabbour; Farhad Ravandi; Hagop Kantarjian; Tapan M. Kadia (Haematologica)
Not available.